Human Resource Management and Lecturer Performance in Islamic Higher Education: The Limited Role of Patience in Organizational Effectiveness - Birru Muqdamien; Wasehudin Wasehudin; Juhji Juhji (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2026)
This study examines the influence of human resource management (HRM) practices and patience on lecturer performance in Islamic higher education institutions. Using a quantitative correlational approach, data were collected from 737 lecturers via a structured questionnaire and analysed in SPSS using descriptive statistics, Spearman's correlation, multiple regression, and the Mann–Whitney U test. The results showed that HRM practices significantly predicted lecturer performance (β = 0.61, p < 0.001), explaining 48% of the variance, while patience did not show a significant direct effect on lecturer performance (p = 0.287). A significant difference was also found between lecturers who only teach and those with additional structural responsibilities. These findings emphasise the importance of HRM systems in enhancing academic effectiveness, suggesting that institutional management has a greater influence on lecturer performance than individual psychological attributes. This study implies that Islamic higher education institutions should prioritise strengthening HRM practices, such as recruitment, training, and performance evaluation, to enhance academic effectiveness. Focusing on a strong HR system has greater potential to improve lecturer performance than relying on individual traits such as patience, making institutional HR development strategies the key to academic success.